1987
DOI: 10.1002/ana.410220511
|View full text |Cite
|
Sign up to set email alerts
|

In vivo 31P and in vitro 1H nuclear magnetic resonance study of hypoglycemia during neonatal seizure

Abstract: To examine the hypothesis that hypoglycemia has an adverse effect on brain energy state during seizure, neonatal dogs were subjected to bicuculline-induced seizure while hyperglycemic, normoglycemic, or hypoglycemic. Cerebral blood flow increased and remained elevated in all animals subjected to seizure, regardless of blood or brain glucose concentration. In vivo 31P nuclear magnetic resonance spectroscopy disclosed a small (10-20%) decrease in adenosine triphosphate levels and a greater (20-40%) decline in ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 22 publications
2
23
0
Order By: Relevance
“…16 Animal models suggest increased morbidity and mortality when hypoxic-ischemic injury and neonatal hypoglycemia coexist compared with hypoxic-ischemic injury alone or isolated neonatal hypoglycemia. 12,13 A cohort of 94 term neonates with encephalopathy showed a 16% incidence of hypoglycemia, associated with increased odds for corticospinal tract injury. 22 Higher rates of hypoglycemia have been associated with greater degrees of encephalopathy, 4 yet in our cohort there was little difference between those with or without hypoglycemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Animal models suggest increased morbidity and mortality when hypoxic-ischemic injury and neonatal hypoglycemia coexist compared with hypoxic-ischemic injury alone or isolated neonatal hypoglycemia. 12,13 A cohort of 94 term neonates with encephalopathy showed a 16% incidence of hypoglycemia, associated with increased odds for corticospinal tract injury. 22 Higher rates of hypoglycemia have been associated with greater degrees of encephalopathy, 4 yet in our cohort there was little difference between those with or without hypoglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] Numerous animal and human studies have suggested that neonatal hypoglycemia in the context of HIE may be more detrimental than either condition alone. [12][13][14] These studies also suggest that lower glucose levels are associated with a higher severity of encephalopathy and a worse outcome at 2 years. 4,14 Neuroimaging studies in neonatal hypoglycemia have shown a correlation between hypoglycemia, parieto-occipital injury, and involvement of the underlying white matter tracts, corpus callosum, and thalamus.…”
mentioning
confidence: 83%
“…The method of preparation has been recently described (6). Mongrel dogs (4-12 days old) were anesthetized with halothane, 1-4%, while undergoing tracheotomy and femoral arterial catheterization.…”
Section: Methodsmentioning
confidence: 99%
“…Anesthesia during the ictus was produced by the seizure itself which results in loss of awareness. The EEG, blood pressure, blood glucose, and blood lactate were monitored during the experiment (6). Experiments were approved by the Yale University Animal Care Committee and carried out with the adherence to "Guiding Principles for the Care of Animals," of the American Physiological Society, and in accordance with federal regulations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation